Anterior Cruciate Ligament Reconstruction Using Bone-Patellar Tendon-Bone Autograft with Remnant Preservation: Comparison of Outcomes According to the Amount of Remnant Tissue - Kim, Sung-Jae; Choi, Chong Hyuk; Chun, Yong-Min; Kim, Sung-Hwan; Lee, Su-Keon; Jung, Woo Seok; Jung, Min (The Journal of Knee Surgery, 2019)
There has been controversy about whether remnant tissue of anterior cruciate ligament (ACL) has to be preserved in ACL reconstruction. The purpose of the study was to compare clinical outcomes between groups of patients who underwent ACL reconstruction with bone-patellar tendon-bone (BPTB) autograft divided according to amount of ACL remnant and investigate effect of remnant preservation on outcomes of ACL reconstruction. A total of 185 patients who underwent ACL reconstruction with BPTB autograft were retrospectively reviewed. Patients were divided into four groups according to proportion of length of remnant tissue of injured ACL covering part of reconstructed ACL to total length of reconstructed ACL: group A included 83 patients with no remnant, group B consisted of 38 patients with remnant of < 1/3, group C consisted of 35 patients with remnant of 1/3 to2/3, and group D consisted of 29 patients with remnant of > 2/3. Primary outcome was International Knee Documentation Committee (IKDC) subjective score. Secondary outcomes were stability, range of motion, patient-reported outcomes determined by Lysholm knee scoring scale and Tegner activity scale, IKDC objective grade, and single hop for distance. Return to activity and near-return to activity were investigated. A minimum follow-up duration was 24 months. There was no statistically significant difference between four groups regarding postoperative anterior translation (p = 0.731), Lysholm knee score (p = 0.599), IKDC objective grade (p > 0.999), hop test (p = 0.878), and near-return to activity (p = 0.193). However, patients of group D had significantly better outcomes in IKDC subjective score (group A = 85.0 ± 5.9, group B = 84.9 ± 8.1, group C = 87.4 ± 6.4, group D = 89.2 ± 8.1, p = 0.017), Tegner activity scale (group A = 5.0 ± 1.1, group B = 5.2 ± 1.0, group C = 5.7 ± 1.3, group D = 5.9 ± 1.0, p = 0.001), and return to activity (group A = 25.3%, group B = 31.6%, group C = 45.7%, group D = 55.2%, p = 0.014). ACL reconstruction using BPTB autograft with remnant preservation did not provide better anterior stability compared with conventional ACL reconstruction. However, preservation of remnant of > 2/3 led to more improved activity-related clinical outcomes than no remnant preservation. In cases with substantial remnant tissue of injured ACL remaining, reconstruction of ACL while preserving as much remnant tissue as possible is recommended. This is a Level III, retrospective comparative therapeutic study.
Keywords: arthroscopy; anterior cruciate ligament; reconstruction; remnant preservation